Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
differential equation > integrating to a natural log?
i'll write what i've done so far but i'm stuck at the end at the *****
so the problem was dy/dx= (x^2 + y x^2) / 3
and i separated the variables and got
(3 dy) / (1+y) = x^2 dx
i integrated both sides and got
3 ln(1+y) + C = (x^3)/3 + C
with the C brought over to the x side, it's still
3 ln(1+y) = (x^3)/3 + C
i need y alone, with no ln, so i raised what was written to be exponants of an e to cancel the ln's
e^ (3 ln(1+y)) = e^ ((x^3)/3 + C)
***********
i can simplify the x side to C e^((x^3)/3),
but what about the y side??
i have no idea because the 3 is there. without the 3, it'd be just 1+y.
so what do i do now?
4 Answers
- 1 decade ago
Go back to when you were separating your variables. You could leave the 3 on the right side with the x's. So you'd get dy/(1+y) = x^2/3 *dx
Now integrating both sides you'll get: ln(1+y) = x^3 + C
Now raise both with the e: e^(ln(1+y)) = e^(x^3 + C) = e^(x^3)*e^C : say e^C = A
This becomes: 1 + y = Ae^x^3
Subtract 1 on both sides to get your final answer: y = Ae^(x^3) - 1
- MichaelLv 51 decade ago
3 ln(1+y) = (x^3)/3 + C
divide both sides by 3 before raising them as exponents of e.
So ln(1+y) = (x^3)/9 + C
Now you will get 1 + y = C e^((x^3)/9), which means that you would have y = C e^((x^3)/9) - 1, but it looks better to me if it is y = -1 + Ce^((x^3)/9) because the C stuff is at the end